Reviewing anti-sodomy laws in Kenya through an inclusive interpretation of article 45(2) of the constitution - Sogunro, Ayodele (University of Pretoria, 2024)
Mini Dissertation (LLM (Sexual and Reproductive Rights in Africa))--University of Pretoria, 2024.